2023
DOI: 10.1111/pala.12669
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary origin of the durophagous pelagic stingray ecomorph

Abstract: Studies of the origin of evolutionary novelties (novel traits, feeding modes, behaviours, ecological niches, etc.) have considered a number of taxa experimenting with new body plans, allowing them to occupy new habitats and exploit new trophic resources. In the marine realm, colonization of pelagic environments by marine fishes occurred recurrently through time. Stingrays (Myliobatiformes) are a diverse clade of batoid fishes commonly known to possess venomous tail stings. Current hypotheses suggest that sting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…Despite being the most speciose groups, Rajiformes and Myliobatiformes have lower disparities and in the case of Myliobatiformes also evolutionary rates. Previous findings from the fin outline shape suggest that members of Myliobatiformes have attained higher disparity (6,7,71). We found that this pattern is not necessarily the same for the basal fin elements.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Despite being the most speciose groups, Rajiformes and Myliobatiformes have lower disparities and in the case of Myliobatiformes also evolutionary rates. Previous findings from the fin outline shape suggest that members of Myliobatiformes have attained higher disparity (6,7,71). We found that this pattern is not necessarily the same for the basal fin elements.…”
Section: Discussionsupporting
confidence: 39%
“…Some of the Cretaceous and Eocene taxa belonging to extant groups display morphologies with a mixture of characters between different orders (72). More recently, the so-called aquilopelagic phenotype has been shown to have had evolved together with many other modifications for durophagy (71). The radial elements of the pectoral fin also evolved differently than the basal supporting skeletal elements of the fin depending on the swimming type of each species (60,89).…”
Section: Discussionmentioning
confidence: 99%